Mitigation of Supply Chain Risk Management in Supply of Production Raw Materials Using the House of Risk (HOR) Method - Yulinda Tarigan; Septa Saniatul Mutmainah (Politeknik Negeri Batam, 2023)
Several risks along the supply chain process will cause various kinds of problems, the flow of the raw material procurement process is determined by the roles of several stakeholders such as purchasing, supply chain, production, customer service, and logistics. This research is focused on determining the risks during the procurement of production raw materials and determining the best way to handle the existing risks. House of Risk (HOR) is a method used in this study, which consists of 2 stages with the first stage determining the risk events and risk agents and determining the priority of the risk agent, the second stage determining the priority of risk mitigation. The results of the first stage of HOR found 23 risk events and 24 risk agents with the highest ARP values were (A2) sudden request changes. In the second stage of HOR with the highest ETDK value (PA1) conducts inventory control.